2016
DOI: 10.1038/cdd.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Merlin inhibits Wnt/β-catenin signaling by blocking LRP6 phosphorylation

Abstract: Merlin, encoded by the NF2 gene, is a tumor suppressor that acts by inhibiting mitogenic signaling and is mutated in Neurofibromatosis type II (NF2) disease, although its molecular mechanism is not fully understood. Here, we observed that Merlin inhibited Wnt/β-catenin signaling by blocking phosphorylation of LRP6, which is necessary for Wnt signal transduction, whereas mutated Merlin in NF2 patients did not. Treatment with Wnt3a enhanced phosphorylation of Ser518 in Merlin via activation of PAK1 in a PIP 2 -d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…Thus, β-catenin avoids degradation by Axin-GSK3β-CK1-APC complexes. In the cytoplasm, β-catenin accumulates and enters the nucleus to activate different genes that regulate cellular proliferation and differentiation (25).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, β-catenin avoids degradation by Axin-GSK3β-CK1-APC complexes. In the cytoplasm, β-catenin accumulates and enters the nucleus to activate different genes that regulate cellular proliferation and differentiation (25).…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory status is reversed when secreted WNT ligands bind to and activate Frizzled (FZD) transmembrane receptor and LRP coreceptor. The ensuing signaling events result in nuclear translocation of β-catenin and together with TCF/LEF transcription factors, culminate in activation of target gene expression [21].…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…The fact that these type of tumors also show some levels of Merlin loss or inactivation [2,24] suggests a connection between Merlin and the WNT/β-catenin pathway. Moreover, Neurofibromatosis type 2 patients with schwannoma, a clinical manifestation of the disorder, accumulate high levels of βcatenin, further indicating that elevated WNT/ β-catenin signaling activity is associated with deficient Merlin expression [21].…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…However, gain of function of the pathway by disruption of the Wnt/β-catenin inhibitor Axin2 can also result in coloboma, with persistent expression of MITF and OTX2 (19) similarly to Nf2 CKO . Importantly, several studies have shown that NF2 can associate with LRP6 and block its phosphorylation resulting in inhibition of Wnt/β-catenin pathway activation (97).…”
Section: Loss Of Nf2 Function Leads To a Narrow Coloboma In The Ventrmentioning
confidence: 99%